Development of a resilient coastal wetlands design framework towards ecotourism education in Setiu Wetland, Malaysia - Aminuddin, Balqis (2024)
This thesis aims to develop a resilient coastal wetland design framework for ecotourism education in Malaysia's Setiu Wetland. The objectives of this research are to (i) identify gaps in the physical design for ecotourism educational experiences, (ii) determine emerging themes from stakeholders to develop a coastal wetland design framework, and (iii) develop indicators for resilient design to improve monitoring and control strategies for ecotourism education. The theories of change, sustainability, and resilience are used with qualitative approaches grounded in constructivism. This study establishes the interlinkages between the physical environment, stakeholders, and educational activities. Triangulation and thematic analysis are used for peer review and expert interpretation. This study reveals 23 physical design and infrastructure deficiencies, including missing signs and empty spaces, that hinder quality ecotourism education. It emphasises the need for sustainable practices, tourism, and environmental education. Resilient design incorporating economic, environmental, and social performance elements and VR-BIM technologies can improve monitoring and control methods. One can establish a complete plan that features technology and community participation for sustainable ecotourism activities at the coastal wetland zone. This research can help the Malaysian Ministry of Education and Tourism promote the coastal wetlands as a globally recognised destination for outdoor education and a high-skilled talent production centre. These activities are estimated to benefit the local community, boost the local economy, and expand the tourist industry.